Evaluation of Diet-Related Infographics on Pinterest for Use of Behavior Change Theories: A Content Analysis - Wilkinson, Jessica L; Strickling, Kate; Payne, Hannah E; Jensen, Kayla C; West, Joshua H (JMIR Publications, 2016)
BackgroundThere is increasing interest in Pinterest as a method of disseminating health information. However, it is unclear whether the health information promoted on Pinterest is evidence-based or incorporates behavior change theory. ObjectivesThe objective of the study was to determine the presence of health behavior theory (HBT) constructs in pins found on Pinterest and assess the relationship between various pin characteristics and the likelihood of inclusion of HBT. MethodsA content analysis was conducted on pins collected from Pinterest identified with the search terms "nutrition infographic" and "healthy eating infographic." The coding rubric included HBT constructs, pin characteristics, and visual communication tools. Each HBT construct was coded as present or not present (yes=1, no=0). A total theory score was calculated by summing the values for each of the 9 constructs (range 0-9). Adjusted regression analysis was used to identify factors associated with the inclusion of health behavior change theory in pins (P<.05). ResultsThe mean total theory score was 2.03 (SD 1.2). Perceived benefits were present most often (170/236, 72%), followed by behavioral capability (123/238, 51.7%) and perceived severity (79/236, 33.5%). The construct that appeared the least was self-regulation/self-control (2/237, 0.8%). Pin characteristics associated with the inclusion of HBT included a large amount of text (P=.01), photographs of real people (P=.001), cartoon pictures of food (P=.01), and the presence of references (P=.001). The number of repins (P=.04), likes (P=.01), and comments (P=.01) were positively associated with the inclusion of HBT. ConclusionsThese findings suggest that current Pinterest infographics targeting healthy eating contain few HBT elements. Health professionals and organizations should create and disseminate infographics that contain more elements of HBT to better influence healthy eating behavior. This may be accomplished by creating pins that use both text and images of people and food in order to portray elements of HBT and convey nutritional information.